Financial instability, cycles and the role of institutions - Aurel Iancu (Romanian Academy, National Institute for Economic Research, 2014)
In this study I review the main scientific contributions of Minsky and other scholars to the financial instability and crisis issues, and the role of institutions in modeling the medium and long financial and business waves. The topics developed in this paper are the following: the relationships between financial instability, financial and business crisis and institutions; the thwarting of the explosive instability by the specific institutions' actions and regulations; the impact of the institutional changes on the financial and business cycles; an empiric approach to the financial and business cycles and their synchronization in the Central and Eastern European countries/ members of the EU, taking into account the main characteristics of the changes in these countries' institutions.
Keywords: B52; D53; G01; G2; L51; P11; P21; P31; 330; financial instability; business cycles; financial cycles; institutions; long waves; basic cycles; supercycles; Central and Eastern European countries